Exon deletions of the phenylalanine hydroxylase gene in Italian hyperphenylalaninemics - Calì, Francesco (Korean Society for Biochemistry and Molecular Biology, 2010)
A consistent finding of many studies describing the spectrum of mutant phenylalanine hydroxylase (PAH) alleles underlying hyperphenylalaninemia is the impossibility of achieving a 100% mutation ascertainment rate using conventional gene-scanning methods. These methods include denaturing gradient gel electrophoresis (DGGE), denaturing high performance liquid chromatography (DHPLC), and direct sequencing. In recent years, it has been shown that a significant proportion of undetermined alleles consist of large deletions overlapping one or more exons. These deletions have been difficult to detect in compound heterozygotes using gene-scanning methods due to a masking effect of the non-deleted allele. To date, no systematic search has been carried out for such exon deletions in Italian patients with phenylketonuria or mild hyperphenylalaninemia. We used multiplex ligation- dependent probe amplification (MLPA), comparative multiplex dosage analysis (CMDA), and real-time PCR to search for both large deletions and duplications of the phenylalanine hydroxylase gene in Italian hyperphenylalaninemia patients. Four deletions removing different phenylalanine hydroxylase (PAH) gene exons were identified in 12 patients. Two of these deletions involving exons 4-5-6-7-8 (systematic name c.353-?_912 + ?del) and exon 6 (systematic name c.510-?_706 + ?del) have not been reported previously. In this study, we show that exon deletion of the PAH gene accounts for 1.7% of all mutant PAH alleles in Italian hyperphenylalaninemics.